Bag of What? Simple Noun Phrase Extraction for Text Analysis - Handler, Abram; Denny, Matthew; Wallach, Hanna; O'Connor, Brendan T. (NLP+CSS@EMNLP, 2016)
Social scientists who do not have specialized natural language processing training often use a unigram bag-of-words (BOW) representation when analyzing text corpora. We offer a new phrase-based method, NPFST, for enriching a unigram BOW. NPFST uses a partof-speech tagger and a finite state transducer to extract multiword phrases to be added to a unigram BOW. We compare NPFST to both ngram and parsing methods in terms of yield, recall, and efficiency. We then demonstrate how to use NPFST for exploratory analyses; it performs well, without configuration, on many different kinds of English text. Finally, we present a case study using NPFST to analyze a new corpus of U.S. congressional bills.